New CD20 alternative splice variants: molecular identification and differential expression within hematological B cell malignancies. Issue 1 (December 2015) - Gamonet, Clémentine; Bole-Richard, Elodie; Delherme, Aurélia; Aubin, François; Toussirot, Eric; Garnache-Ottou, Francine; Godet, Yann; Ysebaert, Loïc; Tournilhac, Olivier; Caroline, Dartigeas; Larosa, Fabrice; Deconinck, Eric; et al.
Abstract Background CD20 is a B cell lineage–specific marker expressed by normal and leukemic B cells and targeted by several antibody immunotherapies. We have previously shown that the protein from a CD20 mRNA splice variant (D393-CD20) is expressed at various levels in leukemic B cells or lymphoma B cells but not in resting, sorted B cells from the peripheral blood of healthy donors. Results Western blot (WB) analysis of B malignancy primary samples showed additional CD20 signals. Deep molecular PCR analysis revealed four new sequences corresponding to in-frame CD20 splice variants (D657-CD20, D618-CD20, D480-CD20, and D177-CD20) matching the length of WB signals. We demonstrated that the cell spliceosome machinery can process ex vivo D480-, D657-, and D618-CD20 transcript variants by involving canonical sites associated with cryptic splice sites. Results of specific and quantitative RT-PCR assays showed that these CD20 splice variants are differentially expressed in B malignancies. Moreover, Epstein–Barr virus (EBV) transformation modified the CD20 splicing profile and mainly increased the D393-CD20 variant transcripts. Finally, investigation of three cohorts of chronic lymphocytic leukemia (CLL) patients showed that the total CD20 splice variant expression was higher in a stage B and C sample collection compared to routinely collected CLL samples or relapsed refractory stage A, B, or C CLL. Conclusion The involvement of these newly discovered alternative CD20 transcript variants in EBV transformation makes them interesting molecular indicators, as does their association with oncogenesis rather than non-oncogenic B cell diseases, differential expression in B cell malignancies, and correlation with CLL stage and some predictive CLL markers. This potential should be investigated in further studies.